Obtenção de cerâmicas porosas de óxido de zinco para aplicação em fotocatálise - Faria, Felipe De Paula (2019)
Photocatalytic processes have been widely used in the decontamination of effluents with dyes. As shown by many authors, semiconductors powders have high photodegradation efficiency. However, the conformation of these materials enables to obtain pieces that can be easily removed after the oxidative process. Thus, this work investigated the production of zinc oxide (ZnO) porous pieces by uniaxial pressing, varying the compression pressure; replica method, with impregnation of different slip in polyurethane foams; and pressing with sacrificial phase, through different percentages and types of organic precursor additives. The samples were burned at 800 and 1000 °C during two hours and characterized by determination of green density (Dv), apparent specific mass (ASM), apparent porosity (AP), water absorption (WA) and scanning electron microscopy (SEM). The porous precursors were characterized by DSC/TG ​​and the slips evaluated by rheological analyzes. With a Rhodamine B solution (5mg/L), the photocatalytic potential of the samples produced was investigated under UVC radiation. UV-Vis Absorption Spectrometry was used to analyze the degradation of dye. In addition to the individual tests, photodegradation cycles were performed to analyze reuse of samples. In general, it was observed that samples with higher porosity mineralized the dye more effectively. On the other hand, temperature influenced directly the properties evaluated; for all the processes, the best results were found at 800 °C. In the uniaxial pressing, the variation of the applied load didn’t show significant changes at the evaluated properties. In the processing by replica, the slip with 65% of ZnO and 1% of thickener produced pieces with high porosity and great levels ​​of photodegradation (90.45%). The sacrificial phase method presented the best results for samples with 25% of eucalyptus sawdust, compacted with 60 MPa. The degradation was equal to 79.45%. All pieces proved to be reusable and the highest levels of mineralization were achieved by ceramics obtained by replica.